Evaluation of the content quality of websites for recurrent aphthous ulcers and oral lichen planus - Xiaosheng Hu; Hui Pan; Wenxiu He; Hong Hua; Zhimin Yan (BMC, 2017)
Abstract Background The Internet is one of the most popular resources for people to obtain medical information; however, only a limited number of studies have reported the quality of the available health information related to oral mucosal diseases. The present study aimed to evaluate the quality of information on websites for recurrent aphthous ulcers (RAU) and oral lichen planus (OLP), in both Chinese and English. Methods Common search engines, BaiDu, Google, and Yahoo in Chinese; and Bing, Google, and Yahoo in English were used to identify websites providing content related to the oral mucosal diseases. The first 100 links for keywords "recurrent aphthous ulcers" and "oral lichen planus" were visited and content was downloaded within 24 h. Two separate trained researchers use the validated DISCERN rating instrument and JAMA benchmarks to evaluate the content. The rating scores were analyzed and the quality was assessed according to the scores and content of websites. Results A total of 145 websites for RAU and 128 of OLP were analyzed. Based on the DISCERN instrument, the quality of the content in websites for both diseases, whether in English or Chinese, was not high, generally scoring 2 to 3 (max. 5). Only 13 of the RAU websites and 21 of the OLP websites fulfilled the four criteria of the JAMA benchmarks. Generally, the scores of the English websites were higher than those of the Chinese websites. During the twelve searches, only four (Yahoo of RAU in Chinese, Bing and Yahoo of RAU in English, and Google of OLP in Chinese) showed moderate correlation between the website's ranking and their rating scores. People cannot obtain high quality medical information if they only look at the top ranked sites on the viewing lists. Websites belonging to universities or medical centers had relatively higher scores compared with the others. Conclusions The quality of the content on websites relating to RAU and OLP in Chinese and English was moderate. More good quality websites and information are needed in the future.